Supported Rhodium (Rh@PS) Catalyzed Benzimidazoles Synthesis Using Ethanol/Methanol as C2H3/CH Source - Sharma, Saurabh; Sharma, Ajay; Yamini; Das, Pralay (Advanced synthesis & catalysis, 2019)
An effective and stable polystyrene supported rhodium (Rh@PS) nano‐catalyst has been synthesized by following reduction‐deposition approach and applied for the selective benzimidazoles synthesis from 1,2‐phenylenediamines and ethanol/methanol as C2H3/CH source. The ethanol/methanol in the presence of trace amounts of aerobic oxygen under Rh@PS catalysed condition, first participated in oxidation of alcohol followed by consecutive condensation, cyclization and hydrogen elimination reactions with 1,2‐phenylenediamine gave the desired products in good yields. The Rh@PS catalyst in a single system performed both oxidation and reduction reactions in a selective/specific manner and applied for large substrate scope. Easy recovery, handling, stability, recyclability of the catalyst and less chance of metal contamination with the products are the added advantages of the process.